A case study of ruptures in overhead ground wire under a large lightning over 400kA. (October 2019) - Liu, Gang; Peng, Xiangyang; Zhong, Meishan; Wang, Rui; Wang, Pengyu; Guo, Deming; Qi, Qi
Abstract: The rupture accident of overhead ground wire (OGW) may happen when the overhead transmission line gets struck by lightning, especially in the case of a large lightning current. This may trigger a short-circuit fault of the overhead transmission line and cause serious harm to the safety and stable operation of the power grid. The Lightning samples are very limited and it is difficult to simulate the actual lightning current in the laboratory accurately. Besides, the standard are short of the consideration to the thermo-mechanical properties of OGW under lightning current. Therefore, it is of considerable significance to study the reason and process of rupture accident of OGW caused by lightning strike. In this paper, a rupture accident of 220 kV OGW happened in Qingyuan, Guangdong Province due to a large lightning strike (475.9kA) is investigated. Firstly, the rupture process of OGW is preliminarily inferred through the fractography analysis of the broken OGW samples. Then, a three-dimensional thermoelectric coupling simulation model of OGW is established, and the melting area and average temperature of each wire of OGW under a lightning strike are calculated. Based on the fractography analysis results and the simulation results of the OGW samples, and taking the correlation between the temperature and the tensile strength of metal material into consideration, a more detailed discussion on the rupture process of OGW is conducted. Finally, the rationality of wire diameter selection for OGW is demonstrated by calculating the residual tensile strength of each wire of OGW under different lightning current. The method for analyzing the rupture accident of OGW caused by lightning strike presented in this paper, which is based on various influencing factors, can provide reference and suggestions for the investigation and solution in similar cases. Highlights: A comprehensive analytical method for the rupture process of overhead ground wire caused by lightning strike is proposed. A model to calculate the melting area for each strand of overhead ground wire during lightning strike is built. A discussion on the rationality of wire diameter selection for overhead ground wire is conducted.